1995
DOI: 10.1111/j.1399-6576.1995.tb04140.x
|View full text |Cite
|
Sign up to set email alerts
|

Premedication with sublingual buprenorphine for out‐patient arthroscopy: reduced need for postoperative pethidine but higher incidence of nausea

Abstract: The effect of preoperative sublingual buprenorphine (B) on postoperative pain (VAS), the need for postoperative opioid injections and on time to discharge, was evaluated in a prospective randomised double-blind study. Forty ASA I-II patients scheduled for arthroscopy of the knee received premedication with 0.4 mg buprenorphine (group B) and 42 patients were given placebo (group P). Postoperatively, pethidine was given to patients with pain. Three of the 40 patients in group B vs 11 of the 42 in group P receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
(8 reference statements)
1
5
0
Order By: Relevance
“…The incidence of postoperative nausea and vomiting was low in all groups. Earlier studies have shown that nausea and vomiting often delay discharge in outpatient surgery (2,6), and that proprofol anaesthesia may reduce the incidence of nausea and vomiting (10). In our study, none of the patients in Goup P and only one in Group E and two in Group S complained of nausea postoperatively, and there was no incidence of vomiting in any of the groups.…”
Section: Prementioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of postoperative nausea and vomiting was low in all groups. Earlier studies have shown that nausea and vomiting often delay discharge in outpatient surgery (2,6), and that proprofol anaesthesia may reduce the incidence of nausea and vomiting (10). In our study, none of the patients in Goup P and only one in Group E and two in Group S complained of nausea postoperatively, and there was no incidence of vomiting in any of the groups.…”
Section: Prementioning
confidence: 99%
“…The ideal choice of anaesthetic technique is still controversial (2,3). The pre-emptive analgesic advantage of regional anaesthesia compared to general anaesthesia is an interesting concept but has yet to be proven (4,5).…”
mentioning
confidence: 99%
“…A total of five RCTs yielding five comparisons were incorporated in the meta-analyses, studying 404 adult patients who received preemptive opioids preoperatively in order to reduce postoperative pain (199 received opioids, 205 received placebo; Table 1; Table 2, notes 16,17) (Juhlin-Dannfelt et al, 1995;Liukkonen et al, 2002;Reiter et al, 2003;WilderSmith et al, 2003;Pozos-Guillen et al, 2007). All five RCTs compared a single opioid group to a single placebo group (Table 1).…”
Section: Opioidsmentioning
confidence: 99%
“…Preoperative administration of opioids resulted in an insignificant reduction in postoperative analgesic consumption (morphine, ketorolac) at 24 h post surgery (five studies, unclear risk of bias across studies) with grand mean effect and 95% CI of À0.32 (À0.81 to 0.18; Table 2). Incorporating only the studies using morphine as postoperative analgesic (Juhlin-Dannfelt et al, 1995;Liukkonen et al, 2002;Reiter et al, 2003;Wilder-Smith et al, 2003) yielded comparable results, namely À0.32 (À0.78 to 0.33). No publication bias was evident for either morphine and ketorolac (Table 2) or morphine alone (t(4) = 0.625; P =0.596).…”
Section: Opioidsmentioning
confidence: 99%
See 1 more Smart Citation